2021
DOI: 10.1002/ps.6323
|View full text |Cite
|
Sign up to set email alerts
|

Seed dressing with triflumezopyrim controls brown planthopper populations by inhibiting feeding behavior, fecundity and enhancing rice plant resistance

Abstract: BACKGROUND Triflumezopyrim (TFM), a novel mesoionic insecticide, has high efficiency at a low dosage, and is mainly used to control hopper species. A previous study demonstrated that seed dressing with TFM effectively controlled rice planthopper populations in mechanically transplanted rice fields; however, mode of action for control was unclear. RESULTS The study shows that seed dressing with TFM resulted in elevated levels of oxalic acid, flavonoids, phenolic substances, callose and other compounds associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…In addition, the weights of female BPHs fed on DCY100-pretreated plants of two rice varieties were decreased significantly (Figure 8), and these results were consistent with those of a previous study [27]. Recent studies have indicated that treating seeds with triflumezopyrim enhanced rice resistance against BPH by inhibiting phloem ingestion, which resulted in the reduced fecundity of females and lowered the population in the field [42,43]. A two-way ANOVA suggested that the effect of DCY treatment on the honeydew excretions and weights of BPHs was greater than rice variety and the interactions between DCY treatment and rice variety (Table 6).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the weights of female BPHs fed on DCY100-pretreated plants of two rice varieties were decreased significantly (Figure 8), and these results were consistent with those of a previous study [27]. Recent studies have indicated that treating seeds with triflumezopyrim enhanced rice resistance against BPH by inhibiting phloem ingestion, which resulted in the reduced fecundity of females and lowered the population in the field [42,43]. A two-way ANOVA suggested that the effect of DCY treatment on the honeydew excretions and weights of BPHs was greater than rice variety and the interactions between DCY treatment and rice variety (Table 6).…”
Section: Discussionsupporting
confidence: 88%
“…The EPG technique is mostly used to study the real-time probing and ingestion behavior of sucking insects, for an insect’s stylet-probing behavior can be recorded by digital signal and afterwards transformed into waveform and then analysis by bundled software. EPG was first applied to research on the feeding behavior of aphids, then widely used in research on the feeding behavior of BPHs [ 13 , 24 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…He et al [8] found that pymetrozine treated rice plants might be distasteful to BPH, observed by a drastic increase in the NP period of electropenetrography (EPG) decreased phloem ingestion. The TFM works by desensitizing the nicotinic acetylcholine receptor [19]. However, pymetrozine interferes with neuroregulation and triggers feeding termination for prick-suck insects, resulting in starvation [8].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the TFM and related mesoionic insecticides, having native and expressed nAChRs, compete for the same binding site as imidacloprid. Further, several other studies have unfolded the role of TFM as a BPH population controlling agent in China [17], India [18], and Malaysia [19]. The TFM showed an effective response and high efficiency to rice planthoppers with no toxicity to non-target arthropods.…”
Section: Introductionmentioning
confidence: 99%